Conjugated Microporous Polymers with Dimensionality‐Controlled Heterostructures for Green Energy Devices. (20th May 2015) - Zhuang, Xiaodong; Gehrig, Dominik; Forler, Nina; Liang, Haiwei; Wagner, Manfred; Hansen, Michael Ryan; Laquai, Frédéric; Zhang, Fan; Feng, Xinliang
<x xml:space="preserve">Abstract</x> Dimensionality for conjugated microporous polymers (CMP‐nD, n = 0, 1, 2) is proven to be of great importance for tailoring their photophysical properties. Moreover, CMP‐nD can further be converted into boron and nitrogen co‐doped porous carbons (nDBN, n = 0, 1, 2) with maintained 0D, 1D, and 2D nanostructures and highly efficient catalytic performance.